Constitutive β cell expression of IL-12 does not perturb self-tolerance but intensifies established autoimmune diabetes - Andreas Holz; Kelly Brett; Michael B.A. Oldstone (The Journal of Clinical Investigation, 2001)
To analyze the function of the Th1-promoting cytokine IL-12 in vivo, we generated transgenic (tg) mice (RIP-IL12 mice) whose pancreatic β cells constitutively express bioactive IL-12 or one of its components, p35 or p40. In contrast to non-tg littermates or single-tg RIP-p35 and RIP-p40 mice, RIP-IL12 mice developed a marked pancreatic infiltration of lymphocytes and macrophages, mainly around islets. Expression of bioactive IL-12 primarily upregulated transcript levels of IFN-inducible protein-10 (IP-10), RANTES, IFN-γ, and TNF-α in the pancreas. Despite the substantial recruitment of mononuclear cells, no biochemical or clinical disease was evident in the exocrine or endocrine pancreas. Coexpression of lymphocytic choriomeningitis virus (LCMV) proteins with IL-12 in the β cells failed to spontaneously activate or expand antigen-specific anti-self/viral T cells in uninfected tg animals. However, when RIP-IL12 × RIP-LCMV tg mice were infected with LCMV, antigen-specific anti-self/viral T cells were induced, which led to an acceleration in the kinetics and severity of insulin-dependent diabetes mellitus (IDDM). Thus, the ectopic expression of IL-12 does not spontaneously break tolerance and activate antigen-specific T cells in the periphery, but it does worsen ongoing autoimmune disease.